Association between physical activity, weight – adjusted waist index, and all – cause mortality in Chinese older adults: a national community – based cohort study - Ren, Kexin; Tao, Yuan; Wang, Meihong (Biology of Sport, 2025)
Enhancing physical activity and managing body weight are crucial for addressing aging -related challenges. However, research on the relationship between physical activity, Weight-Adjusted Waist Index (WWI), and all-cause mortality is limited. This study aims to explore these interactions and their impact on elderly health. Data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) for 2011–2018 included 7,034 residents aged ≥ 60 years. We utilized Cox proportional hazard models to assess the relationships between physical activity, WWI, and all-cause mortality, supplemented by subgroup analyses and interaction tests. We did a mediation analysis to assess how much of the effect of physical activity on survival status was mediated through WWI. Active individuals and those transitioning from inactive to active lifestyles exhibited significantly lower all-cause mortality risks, with reductions of 26% (HR = 0.74, CI: 0.65–0.83) and 9% (HR = 0.91, CI: 0.83–0.99), respectively. A positive correlation was found between WWI and all-cause mortality, with a threshold of 11.38 cm/√kg indicating increased risk. Although no interaction between physical activity and WWI was observed ( P = 0.462), mediation analysis showed that 3.06% of the effect of physical activity on survival status was mediated through WWI. Maintaining physical activity or transitioning from a sedentary lifestyle to an active one can significantly reduce all-cause mortality in the elderly. Moreover, high WWI is associated with an increased risk of death. Importantly, WWI partially mediates the relationship between physical activity and death, shedding light on why physical activity reduces mortality and reinforcing the need for health promotion strategies tailored to the elderly population.